World Economic Outlook, October 1986. (World Economic Outlook; World Economic Outlook ;, 1986)
This paper highlights that economic developments in the first half of 1986 were disappointing in a number of respects. Despite the stimulus from lower interest rates and lower oil prices, the pace of activity in the industrial countries slowed. This contributed to continuing sluggishness in the growth of world trade and a further weakening of primary commodity prices. Falling export earnings in developing countries worsened the outlook for the restoration of generalized creditworthiness and for the resumption of a satisfactory growth performance.